Growth, condition factor, gonadosomatic index and spawning of yellowtail scad (atule mate) in the coastal waters of Pahang, Malaysia - Rahman, Mohammad Mustafizur (2014)
Yellowtail scad (Atule mate) is an economically important food fish in Malaysia but the capture production of this fish is decreasing rapidly in the Malaysian water. In 2006, the total capture production was 24,785 tons, while in 2011, it was 22,682 tons. The total capture production of yellowtail scad has been decreased by about 2000 tons (8%) in 5 years. Unfortunately, there is no initiative and regulation concerning the management of fish species. However, proper management of wild stock is urgently needed to obtain sustainable production of this fish. Before applying any management policies and techniques on any wild fish stock, information on some important characteristics such as growth, condition factor, and spawning are prerequisite. Unfortunately, such information for yellowtail scad in Malaysian coastal water is lacking. Therefore, a study was conducted to understand the growth, condition factor, gonadosomatic index and spawning of yellowtail scad in the coastal waters of Pahang, Malaysia. For this research, a total of 1475 specimens were collected from Kompleks Lembaga Kemajuan Ikan Malaysia (LKIM) from October 2012 to September 2013. The regression analysis of length and weight showed isometric growth (b = 3) for all months except January (2.7024) and March (3.2209). The calculated mean condition factor ranged from 1.100 - 1.266, with a mean value of 1.150 ± 0.053. The highest mean condition factor value was observed in November (1.266) and the lowest was observed in October (1.100). The gonadosomatic index was at its peak in August and lowest in December. Based on the observed GSI of male and female yellowtail scad, spawning season of this fish in the Pahang Coastal water might be March to September. However, more complete study is still needed to confirm this result. There was no relationship between condition factor and gonadosomatic index. These results will be useful for fish biologists and fishery management for suggesting adequate regulations for sustainable fishery management in Malaysian waters and nearby countries.